2017
DOI: 10.1155/2017/8363190
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Storage Capacity and Night Ventilation Performance of a Solar Chimney Combined with Different PCMs

Abstract: Thermal storage capacity and airflow rate of a solar chimney combined with different PCMs are numerically studied during nighttime. PCMs with phase change temperatures of 38°C, 44°C, 50°C, and 63°C are selected in this numerical study. Results show that the maximum average ventilation rate of 610 kg/m 2 and maximum thermal storage of 4750 kJ/m 2 are achieved at the phase change temperature of 38°C. However, for phase change temperature of 63°C, night ventilation does not occur under the identical conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This approach holds immense promise for improving indoor thermal comfort conditions while also reducing reliance on mechanical cooling systems. Studies have shown that integrating phase-change materials with solar chimneys can extend the duration of efficient ventilation even after sunset [68]. PCM possesses unique properties such as high latent heat density and isothermal phase change characteristics, making it an ideal candidate for integration into solar absorbers or chimney designs.…”
Section: Solar Chimney and Ventilator Integrationmentioning
confidence: 99%
“…This approach holds immense promise for improving indoor thermal comfort conditions while also reducing reliance on mechanical cooling systems. Studies have shown that integrating phase-change materials with solar chimneys can extend the duration of efficient ventilation even after sunset [68]. PCM possesses unique properties such as high latent heat density and isothermal phase change characteristics, making it an ideal candidate for integration into solar absorbers or chimney designs.…”
Section: Solar Chimney and Ventilator Integrationmentioning
confidence: 99%
“…Therefore, energy losses analysis is relevant for optimizing solar chimney design. Based on theoretical studies, nearly 50% of the solar energy is lost through glass cover to ambient (Lu et al, 2017). In addition, the absorber plate backside without good thermal insulation reduces system efficiency by up to 60% (Afonso and Oliveira, 2000).…”
Section: Introductionmentioning
confidence: 99%